1988
DOI: 10.1128/aac.32.6.858
|View full text |Cite
|
Sign up to set email alerts
|

Increased efficacy of phosphonoformate and phosphonoacetate inhibition of herpes simplex virus type 2 replication by encapsulation in liposomes

Abstract: Phosphonoformate and phosphonoacetate encapsulated in liposomes have substantially greater activity against herpes simplex virus type 2 in Vero cell tissue culture than the nonencapsulated compounds at the same dose. Encapsulation of phosphonoformate in liposomes resulted in a 30-fold increase of the antiviral effect with no increase in cytotoxicity measured by inhibition of thymidine incorporation into normal Vero cells. Thus, the selectivity of the liposomal drug increased 27-fold compared with the nonencaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This was demonstrated for herpes simplex virusinfected monkey kidney cells or rabbit corneal cells treated with foscarnet or acyclovir (38). Some in vitro studies indicate that intracellular viral infections in nonphagocytic cells can be more effectively treated when the antiviral agent is administered in the liposome-encapsulated form.…”
Section: Targeting Of Antibiotic In Infections Outside the Mononucleamentioning
confidence: 93%
“…This was demonstrated for herpes simplex virusinfected monkey kidney cells or rabbit corneal cells treated with foscarnet or acyclovir (38). Some in vitro studies indicate that intracellular viral infections in nonphagocytic cells can be more effectively treated when the antiviral agent is administered in the liposome-encapsulated form.…”
Section: Targeting Of Antibiotic In Infections Outside the Mononucleamentioning
confidence: 93%
“…Furthermore, LE-PFA was shown to be more effective against herpes simplex virus (type 2) replication than free PFA, without any increase in cytotoxicity (34). It was also demonstrated that the 50% lethal dose (LD 50 ) of amBisome (LE-amphotericin B) in mice was greater than 175 mg/kg (76-fold), compared with 2.3 mg/kg for conventional (free) amphotericin B (30).…”
mentioning
confidence: 84%
“…It was also shown that LE-ganciclovir and LE-PFA had greater anti-CMV activities in human embryonic lung fibroblast cells (3). Furthermore, LE-PFA was shown to be more effective (in Vero cell tissue culture) against herpes simplex virus (type 2) replication than was the free drug, without any increase in cytotoxicity (34).…”
mentioning
confidence: 99%
“…The data obtained from other animal studies on the efficacy of liposome-encapsulated antiviral agents in various models of viral infection, caused by herpes simplex virus, influenza virus, Rauscher murine leukaemia virus, or murine AIDS, are contradictory with respect to the efficacy of antiviral agent when administered in the liposome-encapsulated form [17][18][19]. Also data from in vitro studies in which various cell types infected with various viral strains were exposed to antiviral agent in the free form or liposome-encapsulated form are contradictory [19][20][21]. In some studies antiviral antibody was incorporated into liposomes.…”
Section: Liposome-mediated Delivery Of Antimicrobial Agentsmentioning
confidence: 99%